An Analysis of The Motivation Reflected By The Main Characters In The Movie “42” And Its Personality Influence - Dewi Mutiara Indah Ayu (Deiksis, 2017)
The aim of the research is to find out how motivation is reflected by the main characters in the movie “42”, the effort that Jackie and Rickey make in order to fulfill the needs and to analyze the influence of personality on motivation of the main characters. The writer uses qualitative descriptive research in observing the motivation of the main characters of the Movie “42”. The writer limited the data which are classified them into different level needs based on Maslow’s Hierarchy of Human Need theory. However, the writer sees that the main characters had different level of needs structure as their salient. Such as : As for Jackie, the writer found that from 5 level of Maslow’s Hierarchy of Human Needs, there were 2 salient needs; the belongingness and love needs, and the self-esteem need. As for Rickey, there was just 1 need he had to fulfill; the self-actualization need. The writer also noticed the process to fulfill the needs from one level needs to the higher one was not always in a hundred percent to be fulfilled, otherwise the lower need could partly fulfilled so we could go to the higher one as motivation.   Key words: Motivation, Personality, Racism, Hierarchy of Human Needs